Systematic Review Analysis of Government Policy Implementation of COVID 19 Provision Incentives in Indonesia - Marianus Ruba; Ede Surya Darmawan (International Journal of Social Service and Research (IJSSR), 2023)
The emergence of the COVID-19 pandemic has had a significant impact on health workers, who are on the front lines of the COVID-19 fight. The issue of health worker incentives persists to this day. The occurrence of the COVID-19 pandemic has greatly impacted health workers as the front line in the fight against COVID-19. The problem of incentives for health workers continues to this day. Many factors must be considered by regulators and executors at the national and regional levels, as coordination of providing incentives for health workers is deemed ineffective. These include a failure to absorb the budget allocated for health worker incentives, particularly at the regional level, a large number of health workers complaining that incentives have not been distributed, and a reduction in incentives for those at the forefront of dealing with the COVID-19 pandemic. Furthermore, changing regulatory issues in accelerating the provision of COVID-19 health worker incentives are one of the factors that cause delays in paying health worker incentives. Even though the COVID-19 pandemic is over, it is critical to pay attention to the evaluation of policies for providing health workers incentives for COVID-19 that are not only focused on the time of the COVID-19 pandemic but also on the agenda for providing health workers incentives in general. Google Scholar was used to conduct a systematic review. Articles are then found in the search results that meet the criteria. A systematic search turned up eight articles that best matched the study objectives. The study design, perspective, and results of the evaluation of the COVID-19 health worker incentive policy vary greatly. The COVID-19 incentive program for health workers may be a solution to improving health workers' performance in health services. Delays, regulatory issues, and the availability of funds are all issues that must be addressed at a later date. So that the program's success can reflect the government's success in dealing with COVID-19.